Exporting Japan : politics of emigration toward Latin America - Endō, Toake, 1962- (University of Illinois Press, 2009)
Exporting Japan examines the domestic origins of the Japanese government's policies to promote the emigration of approximately three hundred thousand native Japanese citizens to Latin America between the 1890s and the 1960s. This imperialist policy, spanning two world wars and encompassing both the pre-World War II authoritarian government and the postwar conservative regime, reveals strategic efforts by the Japanese state to control its populace while building an expansive nation beyond its territorial borders. Toake Endoh argues that Japan's emigration policy embodied the state's anxieties over domestic political stability and its intention to remove marginalized and radicalized social groups by relocating them abroad. Documenting the disproportionate focus of the southwest region of Japan as a source of emigrants, Endoh considers the state's motivations in formulating emigration policies that selected certain elements of the Japanese population for "export." She also recounts the situations migrants encountered once they reached Latin America, where they were often met with distrust and violence in the "yellow scare" of the pre-World War II period. --From publisher's description.